Review of The Constitutional Court’s Decision In The Dispute Over PHPU DPD 2024 (Perspective of Wrongful Acts In Civil Law) - Iren Tina br Ginting; Budiman N.P.D. Sinaga (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
This paper aims to examine the extent of the contribution of the Constitutional Court's decision Number 03-03/PHPU.DPD-XXII/2024 related to the dispute over the PHPU of DPD Members 2024 in relation to strengthening constitutional legitimacy in a country that adheres to a democratic system. The decision of the Constitutional Court Number 03-03/PHPU.DPD- XXII/2024 gives great meaning to the protection and advancement of the constitutional democratic system. The Constitutional Court plays an important role in maintaining and overseeing the course of the constitution, this can be seen from the full authority given to this institution to adjudicate at the first and final levels with final and binding decisions. This paper also analyzes the role of the PTUN as the highest judicial institution where in this decision the PTUN's decision was ignored, which caused the PTUN's position to be questioned due to deviations from the law that occurred. In this analysis, the decision of the Constitutional Court ends various political conflicts including closing all the dynamics of political interpretation of law in society